Organizational ethnography and methodological angst: myths and challenges in the field - Yanow, Dvora (Qualitative research in organizations and management, 2009)
Purpose - The purpose of this paper is to assess the myths and challenges in the field of organizational ethnography and methodological angst.Design methodology approach - This paper is initially written as an invited keynote address for the 3rd Annual Joint Symposium on "Current Developments in Ethnographic Research in the Social and Management Sciences" (University of Liverpool Management School and Keele University Institute for Public Policy and Management, Liverpool, September 3-5, 2008). It explores what might be distinctive about organizational ethnography and how that might be different from "anthropological" ethnography. In particular, it engages a kind of collective methodological performance anxiety among organizational studies scholars without formal training in anthropology who do ethnographic research.Findings - The paper argues that it is time to be explicit about a variety of forms of professional angst that many ethnographic researchers within organizational studies carry which have not been discussed.Originality value - The paper is of value to those willing to consider the myths and challenges that need engaging and perhaps uprooting and casting off.